Pengaruh Trust, Customer Satisfaction dan User Flow Experience Terhadap E-Loyalty Generasi Z Pada Pengguna Aplikasi Shopee di Surabaya - PARAHITA, Dwi NIDA; Maduwinarti, Ayun; Ida Pratiwi, Ni Made (Research Journal of Social Science and Economics, 2025)
The purpose of this research is to determine the effect of Trust, Customer Satisfaction and User Flow Experience on E-Loyalty. Shopee ranks first in the percentage of E-Commerce business according to sales media in Surabaya with a total percentage of 4.98%. Millennials are the most disloyal, the most emotional, and the most dissatisfied segment of all other generations. The purpose of this study was to determine the effect of Trust, Customer Satisfaction, and User Flow Experience on electronic E-Loyalty for Shopee application users in Surabaya. This type of research is explanatory research which explains the relationship between research variables by testing hypotheses. This research uses nonprobability sampling with purposive sampling technique. The sample of this research is 100 respondents, the questionnaire is distributed online with certain criteria. The sample consists of respondents who live in Surabaya, generation Z and have used the Shopee application at least twice. This type of research is explanatory with a quantitative approach. The data analysis method in this study is Multiple Linear Regression Analysis using the IBM SPSS Statistics 25 application. The results of this study indicate that trust, customer satisfaction, and user flow experience have a significant effect on the loyalty of Shopee application users. Based on these results, it is suggested that Shopee can place advertisements that can attract the attention of its consumers so that Shopee’s consumer trust can increase.